The Development of Computational Technology and Its Use in Finance - Wu Qianjiao; Lan Rong (2010 2nd International Workshop on Education Technology and Computer Science, 2010)
From the constitution of computation, the main subjects of computer science and technology have been summarized. Meanwhile, the reasons why the developments of software technologies have pushed the computational science be widely used were analyzed. Multiple computing models were discussed base on different computer architectures. Finally, computation as a methodology, two important finance problems, effective financial supervision and high-speed financial product pricing, were solved by distributed and parallel computing.